Mental Health Outcomes and Psychological Support among University Students during the COVID-19 Pandemic in Egypt - Abdel-Aziz, Shaimaa Baher; Emadeldin, Maha; Al Hanafy, Salah Hassan; Amin, Tarek Twafik (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: COVID-19 pandemic has demonstrated the impact of a major public health emergency on mental health. Objective: To assess psychological impact among university students and train them to raise mental health awareness among their peers during the pandemic. Methods: This cross-sectional online survey was carried out over the period of July to September 2020. Study participants were medical and paramedical university students representing students’ union alliance of the Egyptian Youth Initiative (EYI). Non-probability sampling method was used for recruiting the study participants. Key mental health outcomes investigated two weeks prior to the survey were posttraumatic stress symptoms (PTSS), symptoms of depression, anxiety, insomnia, and perceived stress. Based on the preliminary analysis of the online questionnaires. A PhD qualified psychiatrist was assigned to develop the online psychosocial support to the volunteers’ students (N=60) to become facilitators for raising mental awareness among peers and train them how to handle stress. Results: Of the 115 students, 42.6% experienced moderate to severe depression, 21.7% were afflicted with moderate to severe anxiety and 62.7% suffered from sub-threshold to severe insomnia. Perceived Stress Scale analysis showed moderate levels of stress among the study participants. A significant difference was detected between pre and posttest mean scores of the PSS (P=0.001) eight weeks after the training program for psychological support. Conclusions: The findings of this study showed that young people suffered of more than one psychological problems and highlighted the urgent need to develop interventions and preventive strategies to address mental health of college students.